ANALYSIS OF CENTRAL GOVERNMENT FINANCIAL PERFORMANCE BASED ON LKPP - Situmorang, Dokman; Setyawan, Arif (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
The objectives of the Central Government Financial Performance Analysis based on LKPP 2015 to 2019 are as follows: Comparing financial ratios based on government financial reports from the 2014 to the 2019 period. Find out more about the financial performance of the central government during one period of government leadership. Find out more about the condition of government debt, which is currently a hot issue among the public. Knowing that Indonesia's economic development is linked to the government's financial performance. The research approach used is quantitative, which means it emphasizes systematic calculations. The Result The Indonesian government's tax ratio ranged above 10 percent during the last presidential term. However, it should be noted that the government needs other efforts to increase this ratio to 15% as is the international standard